Bimbingan dan Konseling Islam-Multikultural dalam Lingkup Pendidikan - Susanto, Juneadi Dwi; Samsuar (Jurusan Bimbingan dan Penyuluhan Islam, 2025)
The implementation of Islamic guidance and counseling is currently faced with socio-cultural phenomena that are closely related to education, the need for good communication, mutual understanding, different religious concepts, ethnicities, and races forces Islamic guidance and counseling to understand multiculturalism in education, in order to achieve an education that educates the nation's children. The need for multicultural understanding today will help facilitate the achievement of a goal amidst differences. This study aims to find the concept of Islamic-multicultural guidance and counseling in education. This study uses a literature study with a qualitative descriptive approach. This approach is used to focus on data collection and analysis from various literature sources to understand the phenomenon of the transformation of Islamic guidance and counseling in education in depth. Based on the explanation of the concept of Islamic-Multicultural Guidance and Counseling in Education, an understanding of the scientific concept can be drawn that can be used in society. The curriculum provided by universities greatly determines the formation of the personality of its students. The application of the concept of Islamic-Multicultural guidance and counseling in education helps researchers to develop education, through learning media, learning methods, application in counseling techniques or more optimal learning development to face current technological advances that require convenience, such as artificial intelligence (AI).